Predictive value of IGF-1/IGFBP-3 ratio for thyroid nodules in type 2 diabetic mellitus - Liu, Bingxin; Wang, Yanjun (Frontiers in Endocrinology, 2024)
Dear Editor of Frontiers in Endocrinology, I am submitting a manuscript for consideration of publication in Frontiers in Endocrinology. The manuscript is entitled "Predictive value of IGF-1/IGFBP-3 ratio for Thyroid nodules in Type 2 Diabetic Mellitus".It has not been published elsewhere and that it has not been submitted simultaneously for publication elsewhere.In this paper, we report on Predictive value of IGF-1/IGFBP-3 molar ratio for Thyroid nodules in Type 2 Diabetic Mellitus. This is significant because this may be a new method to predict the risk population of Thyroid nodules in Type 2 Diabetic Mellitus, especially in the diagnosis and treatment . At present, the measurement of IGF-1 is limited and can not reflect the bioactive IGF-1. The report of IGF-1/IGFBP-3 ratio has important implications for revealing the unexplored mechanism of IGF-1,IGFBP-3 on thyroid nodules in patients with type 2 diabetes mellitus. The paper should be of interest to readers in the areas of the relationship between IGF-1/IGFBP-3 and Thyroid nodules in Type 2 Diabetic Mellitus.Thank you very much for your consideration.